Efecto de la adición de L-carnitina y piruvato sobre la funcionalidad del espermatozoide equino criopreservado - Olmos Acevedo, R. (2020)
Cryopreservation of equine semen represents an important tool to improve reproductive management, however the use of frozen equine semen is still limited due to the poor tolerance of equine sperm to freezing and thawing processes. The aim of the present study was to evaluate the effect of the addition of L-carnitine and sodium pyruvate to the freezing medium on sperm parameters and pregnancy rates. L-carnitine and sodium pyruvate were added to the freezing medium of the treatment group and cryopreservation was performed with a rapid freezing curve. The samples were thawed and evaluated for sperm mobility, viability, morphology, membrane functionality, and acrosome integrity. To assess pregnancy rates, 20 mares were inseminated. In the results it was observed that the addition of L-carnitine and pyruvate in the post-thawed equine semen did not improve the results in terms of progressive motility and other kinetic parameters. The percentage of acrosome / HOS positive, the percentage of live sperm with intact acrosome, and the percentage of normal sperm were significantly higher in the L-carnitine and pyruvate samples. On the other hand, no improvements in the pregnancy rate were observed compared to that obtained using the semen of the post-thawed control group.